Evaluation of the Facial Recess and Cochlea on the Temporal Bone of Stillbirths regarding the Percutaneous Cochlear Implant - Braga, Gabriela Pereira Bom; Gebrim, Eloisa; Balachandran, Ramya; Noble, Jack; Labadie, Robert; Bento, Ricardo Ferreira (International Archives of Otorhinolaryngology, 2018)
Introduction The literature shows that there are anatomical changes on the temporal bone anatomy during the first four years of life in children. Therefore, we decided to evaluate the temporal bone anatomy regarding the cochlear implant surgery in stillbirths between 32 and 40 weeks of gestational age using computed tomography to simulate the trajectory of the drill to the scala timpani avoiding vital structures.Objectives To measure the distances of the simulated trajectory to the facial recess, cochlea, ossicular chain and tympanic membrane, while performing the minimally invasive cochlear implant technique, using the Improvise imaging software (Vanderbilt University, Nashville, TN, US).Methods An experimental study with 9 stillbirth specimens, with gestational ages ranging between 32 and 40 weeks, undergoing tomographic evaluation with individualization and reconstruction of the labyrinth, facial nerve, ossicular chain, tympanic membrane and cochlea followed by drill path definition to the scala tympani. Improvise was used for the computed tomography (CT) evaluation and for the reconstruction of the structures and trajectory of the drill.Results Range of the distance of the trajectory to the facial nerve: 0.58 to 1.71 mm. to the ossicular chain: 0.38 to 1.49 mm; to the tympanic membrane: 0.85 to 1.96 mm; total range of the distance of the trajectory: 5.92 to 12.65 mm.Conclusion The measurements of the relationship between the drill and the anatomical structures of the middle ear and the simulation of the trajectory showed that the middle ear cavity at 32 weeks was big enough for surgical procedures such as cochlear implants. Although cochlear implantation at birth is not an indication yet, this study shows that the technique may be an option in the future.
Keywords: cochlear implantation; middle ear; hearing loss, sensorineural; temporal bone / anatomy; cochlea; experimental studies